1967
DOI: 10.1063/1.3034021
|View full text |Cite
|
Sign up to set email alerts
|

The discovery of fission

Abstract: THE NEUTRON was discovered in 1932. Why, then, did it take seven years before nuclear fission was found? Fission is obviously a striking phenomenon; it results in a large amount of radioactivity of all kinds and produces fragments that have more than ten times the total ionization of anything previously known. So why did it take so long? The question might be answered best by reviewing the situation in Europe from an experimentalist's point of view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 0 publications
0
10
0
3
Order By: Relevance
“…"In the end it was good solid chemistry that got things on the right track" -with this remark concludes Otto Robert Frisch, one of the key persons in fission history, his reminiscences [1]. Indeed, after four years of difficult experiments aimed at the identification of transuranium elements expected to be heavy homologs of rhenium and platinum metals, an amazingly simple radiochemical experiment performed by Otto Hahn and Fritz Strassmann on December 17, 1938, leads to one of the great discoveries of this century.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…"In the end it was good solid chemistry that got things on the right track" -with this remark concludes Otto Robert Frisch, one of the key persons in fission history, his reminiscences [1]. Indeed, after four years of difficult experiments aimed at the identification of transuranium elements expected to be heavy homologs of rhenium and platinum metals, an amazingly simple radiochemical experiment performed by Otto Hahn and Fritz Strassmann on December 17, 1938, leads to one of the great discoveries of this century.…”
Section: Introductionmentioning
confidence: 89%
“…Lise Meitner meets Otto Robert Frisch at Chistmas 1938 in Kungälv on the western shore of Sweden [1], Through Hahn's letter and an incomplete copy of the typescript of the first paper [2] they are well informed about what has happened. When walking together out in the snow they come upon a straightforward explanation of the novel nuclear process.…”
Section: World-wide Echo Early In 1939: Fission Confirmedmentioning
confidence: 98%
“…Theoretical work was never highly regarded in Marie Curie's laboratory, where Joliot worked. Curie once responded to a theoretical physicist's recommendation that a particular experiment be performed with a comment that they might even perform the experiment in spite of that suggestion 19 . Rutherford and his assistant, James Chadwick, spent ten years trying to find the neutron without success.…”
Section: The Neutron Eramentioning
confidence: 99%
“…He found that his counters "mis-behaved" after the cyclotron was shut off. He "solved" this mal-function by automatically shutting off his counters, once the cyclotron was shut off and never realized that he had missed a fundamental discovery 24 .…”
Section: The Neutron Eramentioning
confidence: 99%
See 1 more Smart Citation